Dame Eileen Younghusband (United Kingdom), President 1961-1968 - Karen Lyons (Social Work & Society, 2008)
Dame Eileen Younghusband died in a car accident on a lecture tour in the USA at a point when preparations had commenced for her 80th Birthday celebrations. Her working life had spanned a significant era in the history of the development of social work and education for the profession in the UK and more widely; and she herself had made a major contribution to these developments. She differs from earlier pioneering figures presented in these historical portraits in representing 'the next generation' of significant women in the history of social work. Nevertheless, she was a pioneer in the sense of initiating radical changes as described later in this portrait.